Predictive Ability of Serum IL-27 Level for Assessing Activity of Antineutrophil Cytoplasmic Antibody-Associated Vasculitis. (19th July 2021) - Yoon, Taejun; Ahn, Sung Soo; Pyo, Jung Yoo; Lee, Lucy Eunju; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won
Abstract : Serum interleukin- (IL-) 27 level has been reported to increase in patients with several autoimmune diseases; however, its significance in patients with antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) is unknown. In this study, we investigated the associations between serum IL-27, laboratory features, and activity of AAV and evaluate the predictive ability of serum IL-27 level for disease activity. This study included 77 AAV patients, and we collected clinical and laboratory data at blood sampling. Inflammation-related variables included white blood cell, neutrophil, lymphocyte and platelet counts, serum albumin, erythrocyte sedimentation rate, and C-reactive protein levels. Serum IL-27 and IL-18 levels were measured from stored sera using Human Magnetic Luminex® assay. High disease activity of AAV was defined as the highest tertile of Birmingham vasculitis activity score (BVAS) (≥11). The mean age of the enrolled patients was 59.9 years, and 38 (49.4%) were diagnosed as microscopic polyangiitis. In the multivariable analysis, serum albumin (β = − 0.419 ) and serum IL-27 level (β = 0.221 ) were significantly associated with BVAS. Furthermore, patients with renal manifestation exhibited higher serum IL-27 (mean 308.7 pg/mL vs. 105.8 pg/mL) and IL-18 levels (mean 376.7 pg/mL vs. 270.4 pg/mL) than those without. On applying the optimal cut-off of serum IL-27 level for predicting high activity, AAV patients with serum IL − 27   level ≥ 300.8  pg/mL had a significantly higher risk for having high disease activity than those with serum IL − 27   level < 300.8  pg/mL (relative risk 3.380, 95% confidence interval 1.223, 9.345, P = 0.016 ). These results suggest that serum IL-27 level is associated with the cross-sectional activity and the presence of renal manifestation and could be used to predict high disease activity in patients with AAV.